IMPLEMENTASI KURIKULUM MERDEKA BELAJAR KAMPUS MERDEKA DI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN - LESTARI, SRI; NURAINI, HERY; WIDIART, ANIEK; FADHILA, SRI AJENG (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2024)
This research aims to evaluate the implementation of the Independent Campus Learning Curriculum at the Faculty of Teacher Training and Education (FKIP) from the perspective of students and field supervisors. The research method used is qualitative with data collection techniques through questionnaires and interviews. The research respondents consisted of six students and three field supervisors from the Syekh-Yusuf Islamic University. The results of the research show that the majority of students agree that the policies, information system and guidebook for Merdeka Belajar Kampus Merdeka (MBKM) are in accordance with the guidelines from the Ministry of Education and Culture. However, several obstacles such as course conversion regulations and inadequate responses from field supervisors are still obstacles in implementing the program. However, all respondents were also greatly helped by the easy access to information from the Ministry of Education and Culture via the YouTube channel. The interview results also showed that all respondents were very happy to take part in MBKM activities, especially the campus teaching program. Recommendations for improvement include converting the maximum value of 20 credits given to study programs, increasing training for supervisors, as well as improving coordination between universities and the Ministry of Education and Culture. ABSTRAKPenelitian ini bertujuan untuk mengevaluasi implementasi Kurikulum Merdeka Belajar Kampus Merdeka di Fakultas Keguruan dan Ilmu Pendidikan (FKIP) dari perspektif mahasiswa dan dosen pembimbing lapangan. Metode penelitian yang digunakan adalah kualitatif dengan teknik pengumpulan data melalui kuesioner dan wawancara. Responden penelitian terdiri dari enam mahasiswa dan tiga dosen pembimbing lapangan dari Universitas Islam Syekh-Yusuf. Hasil penelitian menunjukkan bahwa sebagian besar mahasiswa setuju bahwa kebijakan, sistem informasi, dan buku panduan Merdeka Belajar Kampus Merdeka (MBKM) sudah sesuai dengan pedoman dari Kemendikbud. Namun, beberapa kendala seperti regulasi konversi mata kuliah dan respon dari dosen pembimbing lapangan yang belum maksimal masih menjadi hambatan dalam pelaksanaan program. Meskipun demikian, semua responden juga sangat terbantu dengan kemudahan akses informasi dari Kemendikbud melalui kanal YouTube. Hasil wawancara juga menunjukkan bahwa semua responden sangat senang mengikuti kegiatan MBKM khusunya program kampus mengajar. Rekomendasi untuk perbaikan meliputi konversi nilai maksimal sebesar 20 SKS yang diberikan prodi, peningkatan pelatihan untuk dosen pembimbing, serta peningkatan koordinasi antara universitas dan Kemendikbud